Criminological Review of Cyberbullying Against Content Creator - Jennifer Thejaya; Made Suryajaya; Milka Adam (INTERNATIONAL JOURNAL OF SOCIAL, POLICY AND LAW, 2021)
Abstract: Information and technology are more developing along with the times. With the information and technological advances, social media also occurs, making the social life of each person easier. Social media is often used to facilitate communication, socialization, and obtaining various important information. This makes social media to be a very enjoyable place or platform for most people. However, social media also becomes a horrible place for several people if used to bring down someone. The right of freedom of speech and expression is often used as protection for the perpetrators committing cyberbullying.